2023
DOI: 10.3390/dj11050109
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis: Why the Jawbone?

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) has emerged as a complication of anti-resorptive medications. Despite its low incidence rate, this problem has gained attention in recent years due to its devastating consequences and lack of preventive strategy. The fact that MRONJ incidence has been exclusive to the jawbones, despite the systemic effect of anti-resorptive medications, could be a starting point to unravel the multifactorial pathogenesis of this condition. This review aims to negotiate the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…The importance of the management of these patients, often subjected to multiple therapies, has highlighted the relevance of the management of possible odontogenic infections that can trigger adverse processes such as medication-related osteonecrosis of the jaws [18]. In fact, researchers have recently demonstrated that the focus of this pathology is the inflammatory-infective state of the periodontal and alveolar bone, which is the main clue for the onset of this adverse drug reaction [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the management of these patients, often subjected to multiple therapies, has highlighted the relevance of the management of possible odontogenic infections that can trigger adverse processes such as medication-related osteonecrosis of the jaws [18]. In fact, researchers have recently demonstrated that the focus of this pathology is the inflammatory-infective state of the periodontal and alveolar bone, which is the main clue for the onset of this adverse drug reaction [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Hadaya et al [28] exclusively observed cases in the maxilla (n=43), and Tenore et al [29] found "14 cases in the maxilla and 12 in the mandible. A recent study by Kuehn et al [30] aimed to investigate the localizing factors that render the jawbone uniquely vulnerable to osteonecrosis with long-term antiresorptive therapy". "They noted that among patients receiving anti-resorptive medications, osteonecrosis was never reported in long bones.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was characterized as avascular osteonecrosis triggered by Pamidronate and Zoledronate, as delineated by Marx" [1]. "Subsequently, due to the escalating occurrence of osteonecrotic lesions, the term evolved to bisphosphonaterelated osteonecrosis of the jaws (BRONJ), and the last M.R.O.N.J" [1,2,3]. "MRONJ is typified by necrosis of bone tissue and oral cavity exposure, arising from a metabolic imbalance in the mineral bone matrix induced by these medications.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, there was a robust correlation between the systemic leukocyte activity and the composition of their oral microbiota. In fact, its composition has been observed to be correlated with peripheral blood leukocytes' expression of the RANK, TNF-alpha, and aryl hydrocarbon receptor genes [17][18][19] linked to stress and immunological resilience. Immune system dysfunction theory compared human and rat ONJ necrotic bone samples to healthy patients and non-ONJ locations and revealed significant differences in the quantity and distribution of T-cells.…”
Section: Gamma-delta T Cell Impairmentmentioning
confidence: 99%